Detection of iso‐α‐acids to confirm beer consumption in postmortem specimens. Issue 1 (24th November 2014) - Rodda, Luke N.; Gerostamoulos, Dimitri; Drummer, Olaf H.
<x xml:space="preserve">Abstract</x> Iso‐α‐acids (IAAs) can be used as markers for the consumption of beer. Postmortem specimens from a range of coronial cases were analyzed for IAAs in order to determine the prevalence of beer consumption and any correlation to blood alcohol concentrations (BAC). A total of 130 cases were included in this study including those where beer was mentioned in the case circumstances, cases where beer was not mentioned specifically but alcohol was detected, and cases where neither beer was mentioned nor a positive BAC was present. Available blood, serum, vitreous humour and urine specimens were analyzed. Of the 50 cases where beer was mentioned, 86% had one or more IAAs detected. In cases that only had a positive BAC (n = 60), 57% of these cases also showed the presence of these beer markers. IAAs were detected in specimens obtained from traumatized, burnt, and decomposed cases with a mention of beer consumption or where BAC was positive in blood. No IAAs were detected in cases where BAC was negative. There was little or no correlation between blood IAA concentrations and BAC. This study demonstrates the possible detection of IAAs as a marker for beer consumption. Copyright © 2014 John Wiley & Sons, Ltd.